Estimation of time course in phytochrome photostationary state under artificial light for controlling plant growth - Jishi, Tomohiro (Frontiers in Plant Science, 2024)
A model to estimate the time course of a phytochrome photostationary state (PSS) under an arbitrary light environment was developed. It is the solution of differential equations that use conversion rates between active and inactive forms of previously reported phytochromes. The model estimated that 90% of the PSS changes were completed using approximately 3.4 mmol m -2 of integrated end-of-day far-red light irradiation, and 99% of the changes were completed with approximately 6.9 mmol m -2 irradiation. Although these values were affected by the spectral photon flux density of the far-red light. They were consistent with previous results that examined dose requirements of far-red irradiation. The rate at which the PSS changes approached equilibrium was maximized under a red light, followed by far-red, green, and blue light. This estimation method could be used to control phytochrome responses for horticulture via artificial lighting.